APPLYING COMPUTER ASSISTED LANGUAGE LEARNING (CALL) FOR ENGLISH STUDENTS IN INDONESIA - Pirmani, Pebrina; Agustrianti, Sawitri (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
As technology has been found to be increasingly contributing to language classroom, computer assisted language learning (CALL) has received respectable amount of attention as one of the approaches in teaching and learning foreign language. Computers would never substitute teachers but they offer new opportunities for a better language practice. This paper is aimed to explore what actually the computer language learning (CALL) is and how to apply it in English language classroom. The discussions covered CALL’s definition, history, trend, design, types, and the relation of CALL to language skills and components. All in all, the paper presents the advantages and disadvantages of CALL followed by recommendations for teachers/lecturers on the applying of computer assisted language learning in their language classroom.